The Islamic perspective of lingual dens evaginatus in a mandibular left second premolar: a case report - Kusumawardani, Anisa; Ardini, Yunita Dewi; Hasan, Taufiq Hidayat (Kulliyyah of Medicine, International Islamic University Malaysia, 2016)
Introduction: Dens evaginatus (DE) is a developmental anomaly. It is an extra cusp or tubercle protrudes from the occlusal surface of posterior teeth, as well as the lingual surface of anterior teeth. Tubercles are susceptible to pulp exposure from wear or fracture because of malocclusion, leading to pulpal complications early after eruption. DE may also complicate the process of daily routine oral health care. Case report: A 13-year-old girl presented to our polyclinic with sinus track at the posterior lower left buccal gingiva since 1 year ago. The 35 tooth was sound. At the lingual side there was an accessory tooth in close relation to tooth 35 covered with supra-gingival inflammation. Electric pulp test (EPT) showed that tooth 35 already non vital. Intra-oral periapical (IOPA) radiograph and cone beam computed tomography (CBCT) scan showed an abnormal-appearing root shows DE with radiolucency at the periapical area. Root canal treatment was performed using crown down pressureless (CDP) technique and obturation was done using lateral condensation technique. The tooth was restored using composite restoration. Discussions: DE is a rare condition. It is quite a challenge for dental practitioner since the diagnosis is difficult and the treatment options are limited. In the case of DE with necrotic pulp and periapical abscess, root canal treatment is a treatment of choice. We have to accept and appreciate any gift from Allah SWT whether it is good or bad, no equal divine creation except from Allah SWT. Therefore we need to take care of our oral hygiene to prevent diseases. In every disease there is a cure; we need to try to do the best find the cure and not easily get rid of the tooth and replace it with denture. Conclusion: Early diagnosis of DE can lead to proper treatment which can result in high success rate if it is followed by adequate restoration.